Improvement of Emotional Empathy and Cluster B Personality Disorder Symptoms Associated With Decreased Cocaine Use Severity - Vonmoos, Matthias; Eisenegger, Christoph; Bosch, Oliver G.; Preller, Katrin H.; Hulka, Lea M.; Baumgartner, Markus; Seifritz, Erich; Quednow, Boris B. (Frontiers in Psychiatry, 2019)
Aims: Chronic cocaine users display impaired social cognitive abilities, reduced prosocial behavior, and pronounced cluster B personality disorder (PD) symptoms all contributing to their social dysfunctions in daily life. These social dysfunctions have been proposed as a major factor for maintenance and relapse of stimulant use disorders in general. However, little is known about the reversibility of social cognitive deficits and socially problematic personality facets when stimulant use is reduced or ceased. Therefore, we examined the relation between changing intensity of cocaine use and the development of socio-cognitive functioning and cluster B PD symptomatology over the course of one year. Methods: Social cognition, social decision-making, and cluster B PD symptoms were assessed in 38 cocaine users (19 with increased and 19 with decreased use) and 48 stimulant-naïve healthy controls at baseline and at one-year follow-up. Cocaine use severity was objectively determined by quantitative 6-month hair analyses. The categorization of the two cocaine user groups was based on a combination of absolute (±0.5ng/mg) and relative (±10%) changes in the cocaine hair concentration between baseline and the one-year follow-up. Social cognition was assessed using the Multifaceted Empathy Test (MET) and the Movie for the Assessment of Social Cognition (MASC). A combined Distribution/Dictator Game was applied for assessing social decision-making. Cluster B PD symptoms were measured by a SCID-II PD questionnaire according to DSM-IV. Results: Increased cocaine use was linked to worsened empathy, while decreased cocaine use went along with improved emotional empathy. Moreover, whereas decreased cocaine use was associated with reduced severity of self-reported cluster B PD symptoms, these symptoms remained largely stable in increasers. In contrast to a significant reduction of prosocial behavior at baseline in the combined cocaine user group, specifically decreasers were not statistically distinguishable from controls at the follow-up. Conclusions: Socio-cognitive deficits and cluster B PD symptoms of chronic cocaine users are adaptable over time as they covary with increase or decrease of cocaine use. Hence, abstinence-orientation and training of social cognition and interaction might improve social functioning, and should therefore be important therapeutic elements in cocaine addiction treatment.